‘Compassion Alone Moved Me to Tell This Story’: Orderic Vitalis on the Wreck of the White Ship - Strahl, Harriet Claire (Journal of Medieval History, 2025)
The eight complete contemporary accounts of the 1120 wreck of the White Ship offer a unique opportunity to study emotions, remembrance and the writing of recent history in twelfth-century Anglo-Norman society. This essay analyses and compares Orderic Vitalis’ long, detailed and affective text with other accounts of the wreck and its aftermath at the royal court of Henry I to identify grief and commemoration for victims in a national and local context. It reveals Orderic’s unique, local viewpoint on this nationally significant disaster. All narrative elements in his account reflect upon the theme of duty, prompting readers to commemorate the local victims connected to Orderic’s monastic community. The account itself was an act of duty for Orderic, revealing how he conceived of his Historia Ecclesiastica as a commemorative communal history, and how he saw his role as a monk within both the monastic and wider community.